Effects of ethanolic extract of arrowroot tubers (maranta arundinacea l.) on the level of MDA, SGPT and SGOT in ethanol induced rats - Muhammad Reza Ramadhani; Mochammad Saiful Bachri; Wahyu Widyaningsih (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Background : The exposure of free radicals can induce oxidative stress. In the liver, this process will cause impaired liver function. Oxidative stress can be inhibited by antioxidants. Arrowroot tubers (Maranta arundinacea) contains phenolic, flavonoid, alkaloids and saponin compound that are potential as antioxidants. Objective : Determine the effect of ethanolic extract of arrowroot tubers (Maranta arundinacea) against oxidative stress using the parameter of MDA, SGPT and SGOT level in ethanol-induced rats. Methods : Animal models were divided into 5 groups, in which each group contained 6 rats. Group I (normal) and group II (control) was induced with CMC Na 0,5%. Group III, IV and V were given ethanolic extract of arrowroot tubers in the dosage of 125, 250 and 500 mg/Kg/day respectively. The extract was administered orally for 14 days. Induction of ethanol 5 gram/ KgBW was administered orally 1 hour after the last administration on day 14th except for group I. On day 15th, the animal blood was drawn to measure the levels of SGPT and SGOT, then the animals were sacrificed and their organs were analyzed to measure the levels of MDA in the liver. Data obtained in the form of MDA, SGPT and SGOT levels were statistically analyzed using ANOVA. Results : There is statistically significant difference between the utilization of ethanolic extract of arrowroot tubers (Maranta arundinacea) group with the control group in reducing the concentration of MDA (p<0,05), SGPT, and SGOT (p<0,05). Conclusions : The ethanolic extract of arrowroot tubers (Maranta arundinacea) is able to reduce the concentration of MDA, SGPT and SGOT in ethanol-induced rats.